2008
DOI: 10.1161/circulationaha.107.739938
|View full text |Cite|
|
Sign up to set email alerts
|

Cardioprotective and Vasodilatory Actions of Glucagon-Like Peptide 1 Receptor Are Mediated Through Both Glucagon-Like Peptide 1 Receptor–Dependent and –Independent Pathways

Abstract: Background-The glucagon-like peptide 1 receptor (GLP-1R) is believed to mediate glucoregulatory and cardiovascular effects of the incretin hormone GLP-1(7-36) (GLP-1), which is rapidly degraded by dipeptidyl peptidase-4 (DPP-4) to GLP-1(9-36), a truncated metabolite generally thought to be inactive. Novel drugs for the treatment of diabetes include analogues of GLP-1 and inhibitors of DPP-4; however, the cardiovascular effects of distinct GLP-1 peptides have received limited attention. Methods and Results-Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

38
939
7
23

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 942 publications
(1,007 citation statements)
references
References 48 publications
38
939
7
23
Order By: Relevance
“…To determine whether ER stress contributes to endothelial dysfunction in the setting of DM, we utilized liraglutide, a GLP‐1 analogue, which has been demonstrated to reduce ER stress in cultured endothelial cells exposed to high glucose17 and to exert favorable effects on cardiovascular function in both preclinical and clinical studies 18, 28, 29…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine whether ER stress contributes to endothelial dysfunction in the setting of DM, we utilized liraglutide, a GLP‐1 analogue, which has been demonstrated to reduce ER stress in cultured endothelial cells exposed to high glucose17 and to exert favorable effects on cardiovascular function in both preclinical and clinical studies 18, 28, 29…”
Section: Resultsmentioning
confidence: 99%
“…Liraglutide is a GLP‐1 receptor agonist described to activate different signaling pathways via GLP‐1R‐dependent or independent signals 18. To determine if the effects of liraglutide on the vascular endothelium are mediated through GLP‐1R, freshly isolated endothelial cells from patients with DM were pretreated for 30 minutes with the GLP‐1R antagonist exendin fragment (9–39) before liraglutide and insulin sequential stimulation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Native glucagon‐like peptide‐1 (GLP‐1) is a hormone produced by the L‐cells of the distal ileum and colon in response to the entry of nutrients and destroyed by the circulating dipeptidyl peptidase‐4 (DPP‐4) (Ban et al., 2008). In the past decade, GLP‐1 and its analogs have been introduced as a new class of antidiabetic medications for their pleiotropic effects, including increasing glucose‐dependent insulin secretion, suppressing glucagon secretion, decreasing appetite, and reducing body weight (Park, Lim, Lee & Na, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A functional GLP‐1 receptor (GLP‐1R) is highly expressed in the heart. GLP‐1R agonists and DPP‐4 inhibitors have beneficial effects on the cardiovascular system (Ban et al., 2008; Noyan‐Ashraf et al., 2009; Timmers et al., 2009). Previous studies have shown that GLP‐1 and its analogs protected the heart against ischemia‐reperfusion injury and diabetes mellitus (Tate, Robinson, Green, McDermott & Grieve, 2016; Wang et al., 2013).…”
Section: Introductionmentioning
confidence: 99%